2017
DOI: 10.2337/db17-0391
|View full text |Cite
|
Sign up to set email alerts
|

The Synthetic Microneurotrophin BNN27 Affects Retinal Function in Rats With Streptozotocin-Induced Diabetes

Abstract: BNN27, a C17-spiroepoxy derivative of DHEA, was shown to have antiapoptotic properties via mechanisms involving the nerve growth factor receptors (tropomyosin-related kinase A [TrkA]/neurotrophin receptor p75 [p75]). In this study, we examined the effects of BNN27 on neural/glial cell function, apoptosis, and inflammation in the experimental rat streptozotocin (STZ) model of diabetic retinopathy (DR). The ability of BNN27 to activate the TrkA receptor and regulate p75 expression was investigated. BNN27 (2,10, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
3
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 46 publications
3
54
3
1
Order By: Relevance
“…Our data indicate that BNN27, probably by mimicking NGF action or cooperating with it, enhances the immune response of RD by increasing the numbers of infiltrating macrophages and microglia. Our results are, however, in contrast with two recent studies showing that BNN27 administration can reduce Iba-1 + microglia and pro-inflammatory cytokines in the cuprizone-induced experimental multiple sclerosis (MS) 29 or in the streptozotocin-induced experimental diabetic retinopathy (DR) 30 . At the same time, BNN27 increases anti-inflammatory cytokine, interleukin-10 and -4 (IL-10 and IL-4 respectively), levels in diabetic retinas 30 .…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our data indicate that BNN27, probably by mimicking NGF action or cooperating with it, enhances the immune response of RD by increasing the numbers of infiltrating macrophages and microglia. Our results are, however, in contrast with two recent studies showing that BNN27 administration can reduce Iba-1 + microglia and pro-inflammatory cytokines in the cuprizone-induced experimental multiple sclerosis (MS) 29 or in the streptozotocin-induced experimental diabetic retinopathy (DR) 30 . At the same time, BNN27 increases anti-inflammatory cytokine, interleukin-10 and -4 (IL-10 and IL-4 respectively), levels in diabetic retinas 30 .…”
Section: Discussioncontrasting
confidence: 99%
“…However, given the considerable clinical limitations of DHEA, due to its effects on the endocrine axis and its conversion to multiple androgen and estrogen metabolites 22 25 , several groups have synthesized a handful number of novel DHEA derivatives to mitigate this problem/effect 26 , 54 , 55 . Among them, to the best of our knowledge, only the spiro-analogs of DHEA (BNNs) have been tested and reported to have neuroprotective activity 26 , 27 , 29 , 30 , 56 , 57 . BNN27 can protect PC12 cells from serum deprivation-induced apoptosis 26 , 27 , can reduce TUNEL + cell death in superior cervical ganglia following NGF deprivation 27 and can also diminish caspase-3 mediated cell death in dorsal root ganglia of NGF null embryos 27 , in serum-deprived PC12 cells 27 and in cuprizone 29 - and diabetes 30 -induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased inflammation in the retinas accelerates the progression of DR. 21 Our immunofluorescence assay indicated Figure 3A). Western blotting analysis further confirmed the findings and showed that treatments of diabetic rats with INT-777 significantly lowered GFAP expression in comparison with control group (Figure 3B).…”
Section: Tgr5 Activation Normalizes Inflammatory Responses In the Dmentioning
confidence: 85%